Airflow and aerosol concentration in a ribbed smoked sheet rubber cooperative and improvement of ventilation - Lasman Parulian Purba (Prince of Songkla University, 2013)
Thesis (M.Eng., Mechanical Engineering)--Prince of Songkla University, 2009